2001
DOI: 10.1093/ajcn/74.6.796
|View full text |Cite
|
Sign up to set email alerts
|

Relation between dietary intake, serum concentrations, and retinal concentrations of lutein and zeaxanthin in adults in a Midwest population

Abstract: Retinal carotenoids can be measured in epidemiologic studies. In this study, MPOD was associated with lutein + zeaxanthin in the diet and the serum. Retinal concentrations, however, were influenced by other factors as well. To understand the effect of dietary lutein + zeaxanthin intake on the retina and risk of age-related eye disease, future studies should include measures of macular concentrations of these pigments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
83
4
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 22 publications
20
83
4
4
Order By: Relevance
“…Some studies report that men have higher (13-30%) MPOD than women, whereas others deny any relationship. [27][28][29] The Indian MPOD normative data study found no significant association of overall MPOD with gender (unpublished data), which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies report that men have higher (13-30%) MPOD than women, whereas others deny any relationship. [27][28][29] The Indian MPOD normative data study found no significant association of overall MPOD with gender (unpublished data), which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 89%
“…14,[28][29][30][31][32][33] We found that MPOD was 48% higher in the highest level of dietary intake of carotenoids, which was previously reported to be 19-31%. 14,31,32 The regression model eventually obtained is presented in Table 6.…”
Section: Discussionmentioning
confidence: 72%
“…Serum concentrations for b-carotene and vitamin C were much higher in women than in men, as previously found in numerous studies performed in different countries (Hercberg et al, 1994;Curran-Celentano et al, 2001;De Waart et al, 2001;Wallstrom et al, 2001;Olmedilla et al, 2002). This may be related to the better b-carotene and vitamin C nutrient density for these nutrients usually consumed by women than by men and to some life-type factors observed more in men than in women of the cohort such as smoking or drinking alcoholic beverages, which are known to decrease the b-carotene and vitamin C serum levels.…”
Section: Discussionsupporting
confidence: 82%
“…13,14 Subsequent studies have suggested a number of parameters such as age, diet, percentage body fat, gender and tobacco use [15][16][17][18][19] might be determinants of MP; however, these only account for approximately a third of the variance leaving a significant proportion unexplained. In addition, despite MP's dietary origin only modest correlations exist with serum and dietary levels of L and Z.…”
Section: Introductionmentioning
confidence: 99%